Adrenergic Mechanisms in Myocardial Ischemia 1991
DOI: 10.1007/978-3-662-11038-6_4
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Receptors and the Gs Protein in Myocardial Ischemia and Injury

Abstract: SummaryThe purpose of this study was to explore alterations in the life cycle of adrenergic receptors and the G, protein in the heart of ischemic animals. In initial experiments left anterior descending coronary artery occlusion was performed in guinea pigs. Sarcolemmal (SL) and light vesicle (LV) (presumably intracellular) fractions were prepared. Both fractions contained a substantial number of fJ-adrenergic receptors and lXI-adrenergic receptors: the relative proportion of fJ-adrenergic receptors in LV/SL w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…We determined the contents of cardiac β 1 -AR, Gs protein and cAMP, the important components of β 1 -AR signaling pathway, known to contribute to the cardiac injury induced by ischemia and reperfusion (Maisel et al, 1990;Schomig and Richardt, 1990;Hohl and Li, 1991;Anthonio et al, 2000). In agreement with the previous findings, present results showed that the elevation of ECG ST segment and myocardial infarction were induced in IR group, which was accompanied by the increases in the contents of β 1 -AR, cAMP and Gsα.…”
Section: Discussionsupporting
confidence: 93%
“…We determined the contents of cardiac β 1 -AR, Gs protein and cAMP, the important components of β 1 -AR signaling pathway, known to contribute to the cardiac injury induced by ischemia and reperfusion (Maisel et al, 1990;Schomig and Richardt, 1990;Hohl and Li, 1991;Anthonio et al, 2000). In agreement with the previous findings, present results showed that the elevation of ECG ST segment and myocardial infarction were induced in IR group, which was accompanied by the increases in the contents of β 1 -AR, cAMP and Gsα.…”
Section: Discussionsupporting
confidence: 93%
“…catecholamines, after the onset of myocardial ischemia (15 minutes). 38,39 A previous study also revealed that agonistpromoted internalization and functional uncoupling of the receptors are abolished after acute myocardial ischemia. 38 In addition, strenuous, acute exercise can increase the release of endogenous catecholamines.…”
Section: Discussionmentioning
confidence: 92%
“…New receptors could be synthesised or pre-existing receptors could be externalised. Previous investigators have observed rapid externalisation of myocardial alpha-1 and B-adrenergic receptors accompanied by the local release of endogenous catecholamines after the onset of myocardial ischaemia 22 23…”
Section: Discussionmentioning
confidence: 99%